Design, fabrication, and performance evaluation of an indirect solar-powered vegetable dryer - Md. Shazzad Hossain; Md. Rakibul Islam; Tanjim Ahmed; Al Sani; Md. Sazzat Hossain Sarker; Md. Akhtaruzzaman; S. M. Shamiul Alam (Solar Energy Advances)
Solar energy is a versatile resource that can be harnessed for a wide range of applications, including heating, drying, electricity generation through solar cells, and more. In this context, the study focuses on the design and construction of an indirect solar drying (ISD) system to reduce agricultural product waste and enhance preservation. The system utilizes solar energy to heat air, which is then directed into a drying chamber. Designed to overcome the limitations of traditional sun drying, including sunlight exposure, pest vulnerability, and high mechanical drying cost, this affordable dryer was constructed using locally available materials such as wood, glass, aluminium sheets, and galvanized steel wire tray. The dryer was found to be operated efficiently increasing air temperature in the drying chamber to 51–57 °C from the surrounding temperature of 29–35 °C. Experimental results demonstrated that the dryer could reduce the moisture content of red amaranth, moringa, and coriander leaves at 36.11 %, 25 %, and 15 % respectively within four hours—significantly faster than open sun drying (OSD). Additionally, the dryer preserves the color of the products more effectively. The solar dryer achieved efficiencies of 34.67–39.08 %, with faster drying rates and better model fit than OSD highlighting its viability. Economic analysis shows a payback period of 0.78 years, an attribute of 3.21, and a lifecycle benefit of BDT 255,868 (USD 2,132). With high efficiency, sustainability (energy payback: 4.77 years), and superior heat generation, it outperforms traditional methods. This makes it a cost-effective and sustainable solution for Bangladesh and similar regions.